Effect of femoral fracture stabilization with titanium elastic stable intramedullary nail on haemato-biochemical profiles in young dogs - Shakya, Girraj; Jawre, Shobha; Singh, Randhir; Verma, Yamini; Shahi, A.; Vaish, Rakhi (Indian Journal of Veterinary Surgery, 2026)
Femoral fractures in young dogs pose significant orthopaedic challenges, necessitating comprehensive understanding for effective clinical management. This study aimed to elucidate the hemato-biochemical changes in young dogs undergoing surgical stabilization using the titanium elastic stable intramedullary nail (Ti-ESIN) for femoral fractures. Twelve young dogs with femoral fractures received closed reduction and internal fixation via Ti-ESIN, and their haematological and biochemical parameters were evaluated preoperatively and at multiple postoperative intervals. The results revealed a notable rise in haemoglobin and packed cell volume on day 45, coupled with a significant decrease in total leukocyte counts on day 30 and day 45 postoperatively, indicative of preservation of regional blood circulation with the prevention of infection following the minimally invasive surgical approach. Additionally, fluctuations in mean value of serum calcium and phosphorus were transient in nature and remain within the normal physiologic limits throughout the study period. Bone alkaline phosphatase (BALP) levels underscored the intricate processes of bone healing and turnover during fracture repair. The mean value of BALP significantly higher on day 15 during the study period. These findings provide essential insights into the physiological responses of young dogs to femoral fractures and Ti-ESIN treatment, emphasizing the dynamic adaptation of their bodies to trauma and subsequent surgical intervention.